The Development of Android-Based Learning Media for the CAD Pattern Making Course at Universitas Negeri Padang - Meidina Hastuti; Ernawati; Weni Nelmira; M. Giatman (Postgraduate, University of Mataram, 2025)
This research aims to develop Android-based learning media in the CAD Pattern Making course in response to students' difficulties in understanding the functions of certain tools, such as pleats and cut a part, used in drawing fashion patterns digitally. Previous learning media in the form of video tutorials and job sheets in UNP e-learning are considered less interactive and difficult to access through Android devices, even though the majority of students use Android smartphones in the learning process. This research uses the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, Disseminate), but is limited to the development stage. Media validity was tested by three media experts and three material experts using a validation sheet instrument and analyzed by Aiken's V formula. The validation results showed a score of 0.95 from media experts and 0.99 from material experts, including a very valid category. The developed application presents material in the form of text, videos, interactive quizzes, job sheets, and discussion features. The results of the study indicate that the media is suitable in terms of content and design for use in the context of learning CAD pattern making in the D3 Fashion Design study program at Padang State University.